2015
DOI: 10.1080/19443994.2014.1003978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various frequencies and powers of ultrasound on cleaning of flat sheet membrane during and after microfiltration

Abstract: A B S T R A C TMembrane processing has found many applications in various industries as an advanced method of separating materials in liquid or gas. The greatest obstacle in using membrane filtration technology is fouling, particularly in porous membranes. The fouling phenomenon is the result of organic and inorganic materials depositing on the surface and pores of membrane. In this study, the effect of ultrasound frequency (37, 80 kHz, and tandem) and amplitude of sonication (30, 60, and 90%) were evaluated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
4
6
0
Order By: Relevance
“…Maskooki et al . () obtained similar results in cleaning of flat sheet membrane by ultrasonic waves. They reported that ultrasound irradiation causes to a significant improvement in flux recovery during cleaning of fouled membranes.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Maskooki et al . () obtained similar results in cleaning of flat sheet membrane by ultrasonic waves. They reported that ultrasound irradiation causes to a significant improvement in flux recovery during cleaning of fouled membranes.…”
Section: Resultssupporting
confidence: 63%
“…Evaluating the cleaning effects of ultrasound (US) and gas bubbling (GB) treatments on fouled membranes, forward flushing was performed using deionized water under the US and GB treatments for 30 min (Maskooki et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Maskooki et al . ). The effect of the US ‐assisted is based on detaching the foulants by cavitation and microstream mechanisms (Li et al .…”
Section: Introductionmentioning
confidence: 97%
“…The use of low frequencies of US has been studied as an alternate technology for enhancing permeation flux in filtration processes. US can be used either during the filtration to enhance the permeation or as a cleaning technique to improve the cleaning efficiency (Kyll€ onen et al 2005;Muthukumaran et al 2006;Maskooki et al 2015). The effect of the US -assisted is based on detaching the foulants by cavitation and microstream mechanisms (Li et al 2002;Kobayashi et al 2003;Lamminen et al 2004).…”
Section: Introductionmentioning
confidence: 99%